Essential nuances of translation English proper names in the process of learning a foreign language - Ekaterina A. Pertsevaya (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The research is relevant because it is related to the practical aspects of teaching a foreign language to non-linguistic. The change of the words meaning is one of the most common problems, since it requires not only the understanding of the semantic meaning of the word in the mother tongue but the language studied. The English language seems difficult to learn precisely because its lexical units have some similarities with the words of the Russian language, and as the result, are translated incorrectly. Particular attention is paid to the problem of translating lexical units, especially, [roper names, which are found largely in translated scientific and technical texts, reflecting the latest trends in the research: articles, monographs, manuals. The purpose of the study is to provide students with ready-made and effective versions of the correct methods for translating proper names from English into Russian. To do this, the article highlights the most frequently and successfully used options. All lexical units of this group are divided into three subgroups: proper names (including existing names and surnames), geographical names and company names. The most effective version of the translation into Russian the meaning of these words is the following translation techniques: search for existing equivalents, transcription and transliteration. In real practice, combination of these techniques in the target language is required and its full equivalence with the text in the original language. The practical application of the research results is possible when teaching various aspects of the English language to students of various specialties.